2020
DOI: 10.1038/s41598-020-78979-8
|View full text |Cite
|
Sign up to set email alerts
|

Choose your meals carefully if you need to coexist with a toxic invader

Abstract: Vulnerable native species may survive the impact of a lethally toxic invader by changes in behaviour, physiology and/or morphology. The roles of such mechanisms can be clarified by standardised testing. We recorded behavioural responses of monitor lizards (Varanus panoptes and V. varius) to legs of poisonous cane toads (Rhinella marina) and non-toxic control meals (chicken necks or chicken eggs and sardines) along 1300 and 2500 km transects, encompassing the toad’s 85-year invasion trajectory across Australia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…material 3). When threatened, Cane Toads release toxins from their parotid glands that may be lethal to some Varanidae species (Pettit et al 2020(Pettit et al , 2021aHarvey et al 2022), but genetic testing suggests that four varanids of the subgenera Soterosaurus are physiologically resistant to toad toxins (Pettit et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…material 3). When threatened, Cane Toads release toxins from their parotid glands that may be lethal to some Varanidae species (Pettit et al 2020(Pettit et al , 2021aHarvey et al 2022), but genetic testing suggests that four varanids of the subgenera Soterosaurus are physiologically resistant to toad toxins (Pettit et al 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Research on captive freshwater crocodiles reported rapid aversion learning in response to an initial non-fatal encounter with cane toads as prey 26 . Studies of other vulnerable predators (e.g., red-bellied blacksnakes, Pseudechis porphyriacus ; common planigales, Planigale maculata ; yellow-spotted monitors, Varanus panoptes ) have shown that toad colonisation can induce a rapid and long-sustained aversion to their consumption as prey 1 , 27 , 28 . At least two mechanisms may underpin the elimination of cane toads from diets of these predators: behavioural plasticity (conditioned taste aversion) and natural selection (higher mortality of individuals with a genetically based propensity to consume toads 1 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…2020) and chicken necks (Pettit et al . 2020) have been used successfully to improve detections of other Australian varanids. In light of our observations, we suggest this, in combination with active searches by experts (but see Ward‐Fear et al .…”
Section: Figmentioning
confidence: 99%
“…For this reason, species-specific survey methodologies, which account for the species' ecology and do not rely on the skill level of the observer, should be designed for V. mitchelli. Remote camera traps baited with sardines (Moore et al 2020) and chicken necks (Pettit et al 2020) have been used successfully to improve detections of other Australian varanids. In light of our observations, we suggest this, in combination with active searches by experts (but see Ward-Fear et al 2019), as the most appropriate survey methodology for this species.…”
mentioning
confidence: 99%